2013
DOI: 10.4067/s0716-97602013000100002
|View full text |Cite
|
Sign up to set email alerts
|

Expression of resistin, CXCR3, IP-10, CCR5 and MIP-1α in obese patients with different severity of asthma

Abstract: Asthma studies suggest that alteration in the inflammation pattern may be associated with the severity of asthma. The aim of this study was to compare in vitro the expression of chemokines, chemokine receptors and cytokine production from CD4+ T human lymphocytes of asthmatic, both obese and non-obese patients with different severity levels of asthma. Lymphocytes were labeled with monoclonal anti-human CXCR3/IP-10, MIP-1a/CCR5 antibodies and were analyzed by flow cytometry. Cell culture supernatants were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 26 publications
(18 reference statements)
1
14
0
4
Order By: Relevance
“…This effect might be involved in the activation and infiltration of eosinophils in the airway of asthma, especially in virus induced asthma [ 38 ]. We confirmed that IP-10 negatively correlated with FEV 1 [ 18 , 35 , 39 ].…”
Section: Discussionsupporting
confidence: 75%
“…This effect might be involved in the activation and infiltration of eosinophils in the airway of asthma, especially in virus induced asthma [ 38 ]. We confirmed that IP-10 negatively correlated with FEV 1 [ 18 , 35 , 39 ].…”
Section: Discussionsupporting
confidence: 75%
“…In mouse models of allergy with diet-induced metabolic syndrome, electron microscopy has shown stressed and dysfunctional mitochondria in the bronchial epithelium, leading to AHR even in the absence of allergen exposure(49). Chemokine (C-X-C motif) receptor 3 (CXCR3), involved in immune cell regulation and allergic airway inflammation(50), has also been reported to modulate diet-induced insulin resistance and visceral adipose tissue macrophage infiltration and inflammation in mice(51). As with insulin resistance, some studies have shown that the decline in lung function in some cases precedes the development of metabolic syndrome(52); future studies should try to elucidate whether this is a cause-effect relationship, or whether both are consequences of the same process (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanisms or modifiers (eg, age, gender and type of obesity (general vs central)) of the putative effects of obesity on asthma remain unclear. Obesity has been associated with a pro-inflammatory state in Mexicans, 55 in whom 'obese asthma' has been linked to metabolic syndrome. 56 There has been no adequate clinical trial of weight loss and asthma in Latin America.…”
Section: Diet and Obesitymentioning
confidence: 99%